Impact Assessment of Agricultural Research, Institutional Innovation, and Technology Adoption: Introduction to the Special Section - Maredia, Mywish K.; Shankar, B.; Kelley, T.G.; Stevenson, James R. (Elsevier, 2014)
This article introduces a special section on impact assessment of agricultural research, institutional innovation and technology adoption. It is based on papers presented at a pre-conference workshop held at the International Conference of Agricultural Economists at Foz do Iguaçu, Brazil in August 2012. It briefly reviews the history of impact assessment of agricultural research and discusses the contributions made by each of the papers included in this section towards advancing the theory and practice of assessing the outcomes and impacts of agricultural research for development.